2022
DOI: 10.51248/.v42i2.884
|View full text |Cite
|
Sign up to set email alerts
|

A novel and efficient synthesis of 1, 2, 3,4-tetrahydropyrimidine carboxamide derivatives by Biginelli reaction and their in vitro antibacterial activity

Abstract: Introduction and Aim: An efficient aspect of two step synthesis of tetrahydro pyrimidine carboxamide derivatives were developed by Biginelli reaction. The two-step synthesized 1,2,3,4-tetrahydropyrimidinecarboxamide compounds were evaluated by In-vitro studies like antifungal and bacterial activities. Few compounds were shown excellent zone of inhibition against fungal and Microbial activities.  In this study showed significant effect of antifungal and bacterial action against tetrahydro pyrimidine derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In 2021, Thirunavukkarasu and co-workers synthesized tetrahydropyrimidine carboxamide derivatives in two steps via Biginelli reaction. 34 Tetrahydropyrimidine-5-carboxamide derivatives were obtained in a moderately good yield using para-toluene sulphonic acid (PTSA) as a catalyst, and a mixture of 3-oxo-N-(2-oxo-1,-2-dihydropyrimidin-4-yl)butanamide, arylaldehyde, and urea/thiourea as model substrates in ethanol as a solvent (Scheme 13). Tetrahydropyrimidine derivatives exhibit strong inhibitory effects against Gram-positive bacteria, Candida albicans, and fungi, while specific variants display excellent activity against both Gram-positive and Gram-negative bacteria.…”
Section: S C H E M E 1mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Thirunavukkarasu and co-workers synthesized tetrahydropyrimidine carboxamide derivatives in two steps via Biginelli reaction. 34 Tetrahydropyrimidine-5-carboxamide derivatives were obtained in a moderately good yield using para-toluene sulphonic acid (PTSA) as a catalyst, and a mixture of 3-oxo-N-(2-oxo-1,-2-dihydropyrimidin-4-yl)butanamide, arylaldehyde, and urea/thiourea as model substrates in ethanol as a solvent (Scheme 13). Tetrahydropyrimidine derivatives exhibit strong inhibitory effects against Gram-positive bacteria, Candida albicans, and fungi, while specific variants display excellent activity against both Gram-positive and Gram-negative bacteria.…”
Section: S C H E M E 1mentioning
confidence: 99%
“…In 2021, Thirunavukkarasu and co‐workers synthesized tetrahydropyrimidine carboxamide derivatives in two steps via Biginelli reaction 34 . Tetrahydropyrimidine‐5‐carboxamide derivatives were obtained in a moderately good yield using para ‐toluene sulphonic acid (PTSA) as a catalyst, and a mixture of 3‐oxo‐N‐(2‐oxo‐1,2‐dihydropyrimidin‐4‐yl)butanamide, arylaldehyde, and urea/thiourea as model substrates in ethanol as a solvent (Scheme 13).…”
Section: Using Ethanol As Solventmentioning
confidence: 99%
“…[95] 3.5 | Antioxidant properties As shown in this study, the pyrimidine administered in the form of substituted indole-3-yl and furan linked at the fourth position of the pyrimidine-ring exhibits antibacterial, antioxidant, and antifungal properties, which result in remarkable antifungal, free radical scavenging, and antibacterial effects. [96] 3.6 | DNA binding studies acids, it showed a significant DNA groove binder with a binding energy of −21.32 kJ/mol. [97] 3.7 | Antitubercular properties nitrates.…”
Section: Antidiabetic Propertiesmentioning
confidence: 99%
“…As shown in this study, the pyrimidine administered in the form of substituted indole‐3‐yl and furan linked at the fourth position of the pyrimidine‐ring exhibits antibacterial, antioxidant, and antifungal properties, which result in remarkable antifungal, free radical scavenging, and antibacterial effects. [ 96 ]…”
Section: Biological Applicationsmentioning
confidence: 99%